ANALISIS HUKUM ISLAM TERHADAP PRAKTEK JUAL BELI SALAM DAN IJON DALAM MAQASHID SYARI???AH - Muhammad Yusup (Program Studi Ekonomi Syariah, 2021)
In some areas, the practice of Ijon is common, namely selling fruit on unfruitful trees. Say, two months before the mango season, the vendor has paid for the purchase of mangoes. Now when the harvest season arrives, whatever number of mangoes are on the tree belongs to the pengijon. This kind of buying and selling is prohibited in Islam because it is not clear how many items are being traded. In principle, Islam prohibits buying and selling goods that do not yet exist, even if there are exceptions, it is bai' (buying and selling) greetings with certain limitations. Bai' salam is a sale and purchase with the condition that the buyer pays now for the goods that he will receive in the future. In the example above, the purchase of mangoes before harvest is legal if the quantity, quality, and delivery time are determined. For example,